An Approach to the Evaluation of Persistent Hypereosinophilia in Pediatric Patients - Schwartz, Justin T.; Fulkerson, Patricia C. (Frontiers in Immunology, 2018)
Hypereosinophilia (HE) is currently defined by a peripheral blood absolute eosinophil count (AEC) of ≥ 1500/microL. Although mild blood eosinophilia (AEC 500-1500 cells/microL) is observed relatively frequently within the pediatric population, persistent HE is uncommon and should prompt additional clinical evaluation. While the clinical manifestations and underlying etiologies of HE in adults have been well-characterized, there is a paucity of data on HE in children. Limited evidence suggests that many similarities between adult and pediatric HE likely exist, but some important differences remain between these populations. The evaluation of HE in children can be challenging given the broad differential diagnosis, which includes primary hematologic disorders and secondary eosinophilia where the increased eosinophil levels are propagated by disease states that promote eosinophil production and survival. Based on the underlying etiology, clinical manifestations can range from benign, self-resolving elevations in the AEC to life-threatening disorders with the potential for significant end-organ damage. Given the broad differential diagnosis of HE, it remains essential to systematically approach the evaluation of unexplained HE in children. This review will discuss the differential diagnosis for pediatric HE, highlighting etiologies that are more prevalent in the pediatric population. Additionally, a summary of the epidemiology of pediatric HE will be presented, with focus on some of the differences that exist between pediatric and adult HE. Finally, a directed approach to the diagnostic evaluation of children with HE will be discussed.